The Implementation of Inclusive Education at Sekolah Alam Bireuen (SABIR) - Normawati, Yeni Irma; Ulandary, Yury; Setiawan, Robiansyah; Istiarsyah, Istiarsyah; Maisura, Maisura; Anggraini, Zirlia (Angstrom Centre of Education, 2024)
The aim of research is to find out how inclusive education is implemented at Sekolah Alam Bireuen (SABIR) based on Index for Inclusion. The research uses a qualitative approach with descriptive research type. The subjects of research were 5 teachers. Data collection techniques used questionnaire and interviews. The data analysis technique used in this research was descriptive data analysis with interactive model analysis from Miles and Huberman, namely data reduction, data presentation, and drawing conclusions which are then triangulated. The results of this study show that: 1) SABIR has attempted to create an inclusive learning environment for children with special needs even though the accessibility should be improved and teachers must be given training regarding to individual learning programs’ making ; 2) SABIR has made every effort to mobilize all available resources at the school in implementing inclusive education even though there is a shortage of special teachers. Quality education must be a concern for many parties.